Safety and heart rate changes in Covid-19 patients treated with Remdesivir. (November 2021) - Brunetti, Natale Daniele; Poliseno, Mariacristina; Bottalico, Irene Francesca; Centola, Antonio; Montemurro, Laura; Sica, Salvatore; Santantonio, Teresa; Lo Caputo, Sergio
Highlights: Significant heart rate reduction was observed after Remdesivir. No bradycardia or arrhythmias leading to drug discontinuation occurred. Heart rate reduction was proportional to baseline heart rate values. Less severe conditions were related to lower heart rate levels after Remdesivir. Abstract: Objectives: Limited data are available regarding the occurrence and the extent of cardiac rhythm disturbances in patients with COVID-19 treated with Remdesivir. Methods: We present a case series of 52 patients who underwent daily electrocardiogram (ECG) examination after Remdesivir administration. Results: Compared to baseline, a significant heart rate reduction was observed after initiation of Remdesivir; however, no case of severe bradycardia or arrhythmias leading to significant clinical complications or Remdesivir discontinuation occurred. Heart rate reduction was proportional to baseline heart rate values (r=0.75, p<0.001). By multivariate analysis, a less severe clinical presentation of Covid-19 (beta=0.47, p<0.01) was related to lower heart rate levels observed after Remdesivir administration. Conclusions: Despite a significant reduction in heart rate observed after Remdesivir administration, no severe cardiovascular toxicity was observed in Covid-19 patients, even in the case of cardiovascular comorbidities.